BENTUK DAN PENGGUNAAN GARAM BERYODIUM PADA TINGKAT RUMAHTANGGA - Djoko Kartono; Suryati Kumorowulan; M. Samsudin (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2010)
Background: In the market, salt is available in the form of powder (table salt), granule (raw salt) or bricked (pressed salt). Salt has been used as vehicle for iodine fortification since end of 1970s. This iodised salt is set as the long term strategy to control iodine deficiency. lodised salt is also available in those three forms. lodised salt survey at household level was conducted in 2007 as part of the Basic Health Research (BHR), Ministry of Health. Objectives: To study the form and use of iodized salt at household level. Methods: Data from the lodised salt survey 2007 was used for analysis. Salt sample was taken from households in 30 selected districts/cities through out the country. The 30 districts/cities was randomly selected that based on result of lodised salt survey 2005. Iodine content in salt was determined using titration method. The form of salt used by household was also observed. Results: As much as 20.8% of salt used by household were in the bricked form, 35.8% in the granule form and 43.4% in the powder form. In urban areas, 33.3% of household consume granule form, 18.9% consume bricked form and 47.8% consume powder form. Meanwhile, in rural areas, 37.1% of household consume granule form, 21.9% consume bricked form and 41.0% consume powder form. The mean value of iodine content was the lowest (15.9 ppm) in granule form, followed by bricked form (18.0 ppm) and the highest was powder form (28.3 ppm). Using titration method, 7.8% of salt samples contained less than 5.0 ppm of iodine, and only 24.5% salt contained above 30 ppm. As high as 14.2% salt samples contained between 5.0-9.9 ppm iodine, 27.8% contained between 10.0-19.9 ppm iodine and 25.7% contained between 20.0-29.9 ppm iodine. There were only 0.2% salt that contained no iodine and 1.1% salt contained over 80 ppm iodine. Conclusions: The percentage of household that used salt in the form of powder was higher than those used granule and bricked forms. Iodine content in salt in the form of powder was the highest than those salt in the form of bricked and granule.   Keywords: form, use, iodised salt, household